Pengaruh Aktivitas Manusia Terhadap Kualitas Air Sungai Deli - Esra silaban; Widya Khairunisa; Meilinda Suriani Harefa (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
The Deli River is one of the rivers located in Medan Belawan, Deli Serdang Regency, with an area of ​​48 hectares, a length of 73 kilometers (km), and a width of 5.58 m. People use the river for activities, bathing, washing, transportation, for other purposes. agriculture as well as industry, animal husbandry and other activities. People deliberately throw rubbish into the Deli River, such as used tires, plastic, other junk items that can no longer be used. Various activities around rivers such as transportation facilities, sanitation and hygiene practices of local communities, and fish farming have a negative impact on river quality. If these activities are balanced with high public awareness in preserving the river environment, then the river quality will be relatively good and the water will be clear.